(3QjMGfI GdcJGH hfLYI GdefJGHs - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg GdPi TQY ef GdJhGUd ai PGJg , hGdJYGhf Ydi GJHGY eQVGJg WQjbkG hGVMkG hSjdkG s
(3BNQgG (B:s
(3GdebGe GdPi CZQGVg eQbGI GdMbhb, heNGjdI UGObI GdHQhb adG JRGd JdHS ef BdGFg GcQjeI MdI TGaYI s
(3GdLRA GdChd bWYI efgs
(3fSNI JGSYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B605 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B62 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs